SELF ESTEEM DAN RELASI INTERPERSONAL PENYANDANG TUNA RUNGU DI LEMBAGA DEAF N DUMB - Halimah, Lilim; Noorhalia Elcamila, Faya (HUMANITAS (Jurnal Psikologi Indonesia), 2010)
All members of Institute for Deaf ´N Dumb have undergone coaching and training skills. Infact, not all the members are having a permanent job because of the lack of a chance than others, and feeling less confident that he is able to produce something so that the skills he has was useless. One of these internal variables that a barrier is self-esteem. Self-assessment of deaf persons who consider themselves not able to relate well with others, especially with the normal people. In this research, data collection using a questionnaire Self-Esteem Inventory (SEI), which is constructed based on the theory of the Coopersmith´s self-esteem, as many as 45 items of statements, with the level of reliability in this study was 0.926 for the self-esteem variable, and 0.984 for the interpersonal relationship variable. Data obtained in the form of ordinal and the data processing was using non-parametric statistical method of Spearman Rank. Based on data processing with significance level = 0.05 obtained result rs = 0.439, it means there was a significant relationship between self esteem and interpersonal relationship. This means that the lower the self esteem owned it worse interpersonal relationships of persons with hearing disability.